Hubungan Persepsi Tentang Penyakit Dengan Kepatuhan Minum Obat Penderita Hipertensi - Purwandari, Galuh; Purwandari, Galuh; Hartoyo, Mugi; Hartoyo, Mugi; Metasari, Sherly; Metasari, Sherly (MNJ (Mahakam Nursing Journal), 2024)
Background: Hypertension treatment requires a long period, often lasting a lifetime. Patients frequently experience fatigue in taking medication, leading to non-adherence and treatment discontinuation. Misconceptions about the disease usually influence this non-adherence. This study aims to determine the relationship between illness perception and medication adherence among hypertension patients. Method: The study employed a quantitative approach with a cross-sectional design involving 30 hypertension patients selected through simple random sampling. The instruments used were the Brief Illness Perception Questionnaire and the Morisky Medication Adherence Scale 8. Data analysis was performed using the Spearman Rank test. Results: The results indicated a significant relationship between illness perception and medication adherence (p = 0.000), with a strong positive correlation (r = 0.916). Conclusion: The better the patient’s perception of hypertension, the higher the level of medication adherence. This study is expected to be a reference for promoting positive perceptions of hypertension, leading to improved treatment adherence.